Surface modification of carbon fibres with electroactive PEDOT/epoxy composites - Huner, Keziban; Dolas, Hacer; Sarac, A. Sezai (INDIAN ACAD SCIENCES, 2022)
The surface properties of polyacrylonitrile-based (PAN-based) carbon fibres (CFs) mainly control the interfacial strength of CF-reinforced polymer composites. These composites were generally made by commercial high strength fibres with a commercial oxidative treatment. The structure of the interface depends on the nature of the surface treatment. An efficient method to obtain better interfacial surface properties of CF for further functionalization is proposed as electropolymerizing with epoxy-conductive polymer-based composites on the CF surface. In this study, the surface is electrochemically functionalized with poly(3,4-ethylenedioxythiophene) (PEDOT) and epoxy, and they have been characterized by Fourier transform infrared-attenuated total reflectance spectrophotometer, electrochemical impedance spectroscopy. Morphologies were examined by scanning electron microscopy and atomic force microscope, and elemental analysis was performed by energy-dispersive X-ray spectroscopy and their electrochemical properties compared with commercial CFs. Electrochemically coated CFs have increased capacitative property and surface roughness.
Keywords: Carbon fibres; surface modification; electrodeposition; poly(3; 4-ethylenedioxythiophene); epoxy; INTERFACIAL PROPERTIES; SHEAR-STRENGTH; MATRIX; COPOLYMERS; ADHESION; XPS; Materials Science